2004
DOI: 10.1093/jn/134.10.2499
|View full text |Cite
|
Sign up to set email alerts
|

The Hypoglycemic Effects of Hesperidin and Naringin Are Partly Mediated by Hepatic Glucose-Regulating Enzymes in C57BL/KsJ-db/db Mice

Abstract: Dietary antioxidant compounds such as bioflavonoids may offer some protection against the early stage of diabetes mellitus and the development of complications. We investigated the effect of citrus bioflavonoids on blood glucose level, hepatic glucose-regulating enzymes activities, hepatic glycogen concentration, and plasma insulin levels, and assessed the relations between plasma leptin and body weight, blood glucose, and plasma insulin. Male C57BL/KsJ-db/db mice (db/db mice, 5 wk old), an animal model for ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
192
1
4

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 313 publications
(214 citation statements)
references
References 30 publications
17
192
1
4
Order By: Relevance
“…The improvement of leptin resistance in the HFISO group was correlated with body weight and plasma insulin level. 42) The free radical scavenging properties of isflavone are dependent on its polyphenolic structures, which function as donors of hydrogen atoms to deleterious Notes: CON, basal diet group; HF, high-fat diet group; HFISO, isoflavone mixture-added high-fat diet group. GSH, glutathione reduced form; and GSSG, glutathione oxidized form.…”
Section: Discussionmentioning
confidence: 99%
“…The improvement of leptin resistance in the HFISO group was correlated with body weight and plasma insulin level. 42) The free radical scavenging properties of isflavone are dependent on its polyphenolic structures, which function as donors of hydrogen atoms to deleterious Notes: CON, basal diet group; HF, high-fat diet group; HFISO, isoflavone mixture-added high-fat diet group. GSH, glutathione reduced form; and GSSG, glutathione oxidized form.…”
Section: Discussionmentioning
confidence: 99%
“…The content of hepatic glycogen was determined by a commercially available assay kit based on the anthrone reagent method (Jung et al 2004). In brief, glycogen was precipitated with anhydrous ethanol and dehydrated by 98% H 2 SO 4 in order to generate furfural derivatives, which may produce a blue compound after reacting with anthrone.…”
Section: Measurement Of Hepatic Glycogenmentioning
confidence: 99%
“…One of the most abundant bioactive flavonoids is the glycoside naringin, responsible for the bitter taste in grapefruit, which is hydrolyzed to naringenin (4,5,7-trihydroxy-flavanone-7 rhamnoglucoside, Nar) by the gut flora prior to being absorbed by enterocytes. Naringenin protective effects have been widely studied: antioxidant effects (Renugadevi and Prabu 2009), modulation of cytochrome P450 detoxification enzymes (Huong et al 2006), modulation of plasma cholesterol levels (Jeon et al 2007), and antihyperglycemic effects (Jung et al 2004) have been reported. In addition, several experimental data support anticarcinogenic and pro-apoptotic effects of Nar in numerous types of cancer (Arul and Subramanian 2013;Meiyanto et al 2012;Weng and Yen 2012).…”
Section: Introductionmentioning
confidence: 99%